Conceptualising the setting up of a professional learning community for teachers’ pedagogical learning - Feldman, Jennifer (South African Journal of Higher Education, 2016)
This article focuses on the conceptual bases that have informed the establishment and functioning of a professional learning community (PLC) that involves a university lecturer and tutor (the two authors of the article) and a number of practising teachers. The article is a discussion of the intellectual approaches on which the PLC has been founded. Our starting assumption is that teachers’ pedagogical learning requires a supportive and deliberative set of conversations about the intellectual terms and pedagogical capacitation needed for such change. We argue that PLCs are able to provide the reflexive dialogical space, based on action research approaches, for engaging in pedagogical learning. Our on-going PLC is not primarily interested in results-orientated teaching outcomes. Instead, we favour an experimental, messy and recursive conversation that focuses on improving teachers’ classroom teaching. The article considers the terms upon which a social justice oriented approach to pedagogical learning and adaptation might be pursued in a PLC. Inspired by the lenses of theorist, Pierre Bourdieu, we offer a view of PLCs as ‘habitus engagement’, to describe the ways in which our dialogical processing in the PLC might engender pedagogies that induct students into subject knowledge by working with students’ lifeworld contexts and knowledges. We develop an argument for the use of a Funds of Knowledge approach as a way of engaging students meaningfully in their learning. The PLC is conceptualised as a safe dialogical space where the participating teachers are able to develop the conceptual capacity and intellectual skills to develop such a social justice approach to their classroom pedagogy.